The impact of biofilm formation and multidrug resistance on environmental survival of clinical and environmental isolates of Acinetobacter baumannii. - Greene, Christine (Am J Infect Control, 2016)
BACKGROUND. Acinetobacter baumannii is a gram-negative, opportunistic pathogen. Its ability to form biofilm and increasing resistance to antibiotics present challenges for infection control. A better understanding of the impact of biofilm formation and antibiotic resistance on environmental persistence of A. baumannii in hospital settings is needed for more effective infection control. METHODS. A. baumannii strains isolated from patients and the hospital environment were identified via MALDI-TOF mass spectrometry, rep-PCR genotyped, and antibiotic resistance was determined using Vitek®2. Biofilm mass was quantified via microtiter plate method and desiccation tolerance determined up to 56 days. RESULTS. High biofilm forming, clinical, MDR positive strains were 50% less likely to die of desiccation than low biofilm, non-MDR strains. In contrast, environmental, MDR positive, low biofilm forming strains had a 2.7 times increase in risk of cell death due to desiccation compared to their MDR negative counterparts. MDR negative, high biofilm forming environmental strains had a 60% decrease in risk compared to their low biofilm forming counterparts. CONCLUSIONS. The MDR positive phenotype was deleterious for environmental strains and the high biofilm phenotype was critical for survival. This study provides evidence of the trade-off between antibiotic resistance and desiccation tolerance, driven by condition-dependent adaptation, and establishes rationale for research into the genetic basis of the variation in fitness cost between clinical and environmental isolates.